Astragaloside IV (ASIV) Mediates Endothelial Progenitor Cell (EPC) Exosomal LINC01963 to Inhibit Pyroptosis and Oxidative Stress in High Glucose-impaired Endothelial Cells - Xiong, Wu; Zhang, Xi; Zhou, Jian-da; Tan, Mei-xin; Liu, Yu; Yan, Yu; Lei, Hua-Juan; Peng, Jia-rui; Liu, Wei; Tan, Pei (Current Molecular Medicine, 2024)
Background: Hyperglycemia is widespread in the world's population, increasing the risk of many diseases. This study aimed to explore the regulatory effect and mechanism of astragaloside IV (ASIV)-mediated endothelial progenitor cells (EPCs) exosomal LINC01963 in endothelial cells (HUVECs) impaired by high glucose.Methods: Morphologies of exosomes were observed by light microscope and electron microscope. Immunofluorescence was used to identify EPCs and detect the expressions of caspase-1. LINC01963 was detected by quantitative reverse transcription PCR. NLRP3, ASC, and caspase-3 were detected by Western Blot. Nanoparticle tracking analysis was carried out to analyze the exosome diameter. High-throughput sequencing was applied to screen target lncRNAs. The proliferation of endothelial cells was measured by cell counting kit-8 assay. The apoptosis level of HUVECs was detected by flow cytometry and TdT-mediated dUTP Nick-End labeling. The levels of IL- 1β, IL-18, ROS, SOD, MDA, and LDH were measured by enzyme-linked immunosorbent assay.Results: ASIV could promote the secretion of the EPC exosome. LINC01963 was obtained by high-throughput sequencing. It was observed that high glucose could inhibit the proliferation, reduce the level of SOD, the expression of NLRP3, ASC, and caspase- 1, increase the levels of IL-1β, IL-18, ROS, MDA, and LDH, and promote apoptosis of HUVECs. Whereas LINC01963 could inhibit the apoptosis of HUVECs, the increase the expression of NLRP3, ASC, and caspase-1, and decrease the levels of IL-1β, IL-18, ROS, MDA, and LDH.Conclusion: EPCs exosomal LINC01963 play an inhibitory role in high glucoseinduced pyroptosis and oxidative stress of HUVECs. This study provides new ideas and directions for treating hyperglycemia and researching exosomal lncRNAs.
Keywords: exosome